Comportamento de vigas de aço em incêndio com deformação térmica restringida - Nascimento, Julia Souza (2017)
Steel beams tend to elongate in fire. In real structures, this behavior is axially restrained by the adjacent parts of the whole frame which can also impose rotational restraint according to the type of connection between them. These restraints induce significant forces in the beam, which already has the resistance reduced due to thermal degradation of its mechanical and physical properties. The focus of this study is evaluating the behavior of axially and rotationally restrained steel beam on fire. A finite element model was validated against experimental data of a test developed at the University of Manchester. The validated model was used to carry out a set of a parametric study using ANSYS 17.0. The parameters investigated include beam section, beam span, load level and levels of axial and rotational spring stiffness at the beam ends. The maximum temperature values numerically obtained were compared with the formulation of the ABNT NBR 14323:2013